Effect of Listener Head Position on Speech Intelligibility in an Automotive Cabin - LIANG, Linda; LIAO, Linghui; SUN, Jiahui; LIU, Lingling; OU, Liuying; HUANG, Xiaoyue (Archives of Acoustics, 2025)
When evaluating speech intelligibility (SI) in automotive cabins, binaural measurements typically employ a fixed dummy head. However, the impact of listener head positions on SI in nonuniform cabin sound fields remains unclear. This study analyzed SI under various listener head positions in an automotive cabin. An artificial mouth was regarded as the speaker, which was placed in three passenger positions. Binaural room impulse responses were measured using a dummy head in the driver’s seat with various head positions. The results show that head position significantly affects SI, with variations of up to 7 dB in octave band magnitudes, more than one just-noticeable difference in the speech transmission index, and shifts of up to 2.5 dB in the speech-reception threshold. SI variability depends on the speaker’s location. Directivity patterns play a crucial role in the front-passenger position, while seat occlusion affects SI at the back-right position, causing substantial decreases below a certain height threshold. At the back-left position, head positions close to the headrest enhance SI due to distance and reflections. Minor head displacements (4 cm apart) generally have insignificant effects on SI, except near seat obstructions or reach critical thresholds.